Histopathological study of renal hypertension with avocado leaf extract and fractional in male wistar rats - Novi, elisa; Advistasari, Yustisia Dian; Lepangkari, Jaka Sepriantor; Sari, Wulan Kartika (Riset Informasi Kesehatan, 2024)
Background: The first of the cardiovascular diseases that may turn deadly is hypertension, which has elevated blood pressure. The causes of hypertension, which causes an average rise of 140/90 mmHg, are based on epidemiological factors such as stroke, heart failure, myocardial infarction, arterial fibrillation, and peripheral artery disease. Hypertension is also known as the silent killer. Objective: Known histopathology in kidney cells and avocado leaf compounds that could potentially inhibit hypertension. Methods: Methods that can be used in histopathological testing with hematoxylin and eosin (HE) dying and compound determination by analysis Gas Chromatography-Spectrometry Mass (GC-MS) Results: The study obtained GC-MS (Gas Chromatography-Spectrometry Mass) analysis results at an area of 36.50%, molecular weight 17,03 with 9-Octadecenoic acid compounds, and an area of 10,18%, molécular weight 2,54 with a compound of 9-Oktadecenosic acid (z)-methyl esters (CAS). An extract of 250 mg/kgBW has a slightly low renal cell damage value (138), and an effective avocado leaf fraction test is ethanol acetate 250 mg/kgBW, with a small renal cell damage value (146), where as a negative control has a high renal cell damage value (189).